2016
DOI: 10.1002/ep.12503
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and reaction atmosphere effects on the properties of corn stover biochar

Abstract: Biochar properties can vary widely depending on feedstock and processing conditions, which can make meaningful comparisons between biochars difficult. Clear trends can be observed in slow pyrolysis biochar properties over a 300–800°C range of highest treatment temperatures (HTT). These trends, however, are much less consistent for biochars made under slightly oxidizing conditions, such as in gasification and internally‐heated kiln carbonization processes. In this study, slow pyrolysis biochars were produced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Red oak ( Quercus rubra ) and corn stover (Zea mays) feedstocks were slow-pyrolyzed at 400, 500 and 600 °C to produce a total of six biochars. Slow pyrolysis was conducted in a N 2 -purged muffle furnace (Thermo-Scientific; Lindberg/Blue M Moldatherm box furnace) 32 . About 500 g of each air-dry feedstock (particle size < 2 mm) was placed into a steel box (24 cm × 14 cm × 15 cm) within the muffle furnace; an N 2 purge line was inserted through the furnace and into the box, and the box was purged for 30 min at 1500 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red oak ( Quercus rubra ) and corn stover (Zea mays) feedstocks were slow-pyrolyzed at 400, 500 and 600 °C to produce a total of six biochars. Slow pyrolysis was conducted in a N 2 -purged muffle furnace (Thermo-Scientific; Lindberg/Blue M Moldatherm box furnace) 32 . About 500 g of each air-dry feedstock (particle size < 2 mm) was placed into a steel box (24 cm × 14 cm × 15 cm) within the muffle furnace; an N 2 purge line was inserted through the furnace and into the box, and the box was purged for 30 min at 1500 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…About 500 g of each air-dry feedstock (particle size < 2 mm) was placed into a steel box (24 cm × 14 cm × 15 cm) within the muffle furnace; an N 2 purge line was inserted through the furnace and into the box, and the box was purged for 30 min at 1500 mL min −1 . For the pyrolysis reaction, the purge rate was decreased to 40 mL min −1 , the furnace was initially heated at 10 °C min −1 to a temperature 100 °C below the target temperature (300 °C, 400 °C or 500 °C), held for 2 hr, and then heated to the final temperature (e.g., 400, 500 and 600 °C) at 0.5 °C min −1 32 . The highest treatment temperature was held for 2 hr, then the furnace was allowed to cool overnight under N 2 -purge (40 mL min −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gai et al reported similar trends but lower values of surface areas that only reach a maximum of 70 m 2 /g at 700°C . On the other hand, the CEC of biochars, one of the better predictors of their NH4+ adsorption capacity, declines with increasing temperature as the more severe pyrolysis conditions strip the biochar surface of O‐ and H‐containing functional groups …”
Section: Model Developmentmentioning
confidence: 85%
“…Highly alkaline and porous biochar (HAP) is a result of the addition of 95% of N2 and 5% of O2 during a pyrolysis process [32]. HAP has a high pH, which potentially can be effective in mitigating emissions of H2S and volatile fatty acids (VFAs).…”
Section: Introductionmentioning
confidence: 99%